2020
DOI: 10.26710/jbsee.v6i1.1072
|View full text |Cite
|
Sign up to set email alerts
|

Nexus between Economy, Agriculture, Population, Renewable Energy and CO2 Emissions: Evidence from Asia-Pacific Countries

Abstract: This study uses panel co-integration methods and Granger causality examines to scrutinize the dynamic causal relationship between carbon dioxide (CO2) emissions, gross domestic product (GDP), renewable energy (RE), agriculture value added (AVA) and population for the thirteen developed and developing Asia Pacific countries (APCs) covering the period 2005-2017. The results evaluate in two ways: in the short-run, Granger causality test (GCT) is operating from AVA to GDP and express bidirectional causation among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…Energy policies and energy management practices have also been the subject of interest in Pakistan [6][7][8][37][38][39][40][41][42][43][44][45][46]. Mirjat et al [37] argued that government policies since independence varied over time and had been less integrated without the use of energy modeling tools e.g., LEAP, MARKAL/TIMES, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy policies and energy management practices have also been the subject of interest in Pakistan [6][7][8][37][38][39][40][41][42][43][44][45][46]. Mirjat et al [37] argued that government policies since independence varied over time and had been less integrated without the use of energy modeling tools e.g., LEAP, MARKAL/TIMES, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, they emphasized the need for energy modeling for realizing sustainable energy policies to coup with the energy crisis. Latif et al [38] used the MARKAL approach from 2014 to 2035 for renewable and non-renewable energy scenarios, and showed that for Pakistan renewable sources are the best option in reducing energy-related risks and fossil fuel import bills, and at the same time enhances economic and environmental sustainability. In studies by Rafique et al [39,40], the need and prospects of new sources, such as renewable energy have been emphasized to have a sustainable power development and its implementation in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have studied the nexus between agriculture value addition, energy use, economic growth, and emissions in the context of different countries [ 60 , 88 , 98 , 99 , 100 , 101 ]. However, this study differs from the existing literature by complementing it and considering the relationship between agricultural ecosystems and Bangladesh’s environmental degradation from 1985 to 2017.…”
Section: Resultsmentioning
confidence: 99%
“…(4) Gross domestic product (GDP) represents the level of regional economic development. Agricultural output value is an important part of regional GDP [ 55 ]. The improvement of regional economic development level will increase the investment in agriculture, and the regional difference of agricultural output value will narrow, which indicates that the convergence trend of virtual cultivated land among regions will accelerate.…”
Section: Resultsmentioning
confidence: 99%